2017
DOI: 10.1016/j.chemosphere.2017.03.062
|View full text |Cite
|
Sign up to set email alerts
|

Dermal exposure of applicators to chlorpyrifos on rice farms in Ghana

Abstract: Studies evaluating dermal exposure to pesticides among applicators in tropical countries have largely been conducted using the patch dosimetry and hand wiping/washing techniques. This study used the more accurate whole-body dosimetry technique to evaluate dermal exposure to chlorpyrifos among applicators on rice farms in Ghana. The exposure levels were plotted as Cumulative Probability Distribution (CPD). Total Dermal Exposure (TDE) of chlorpyrifos among the median exposed and the 5% highly exposed groups duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…Here, when spraying onto lower crops (about 80-100 cm high), workers are exposed while moving. 20 Thus, the pesticide exposure observed within the present study (with low-lying Korean cabbage, spraying in a downward trajectory with a long wand sprayer) was robust on the legs. These results are similar to those obtained by Nuyttens et al, 21 who reported that downward spraying on tomatoes resulted in greater exposure to the upper leg, which was significantly greater than for other body parts.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…Here, when spraying onto lower crops (about 80-100 cm high), workers are exposed while moving. 20 Thus, the pesticide exposure observed within the present study (with low-lying Korean cabbage, spraying in a downward trajectory with a long wand sprayer) was robust on the legs. These results are similar to those obtained by Nuyttens et al, 21 who reported that downward spraying on tomatoes resulted in greater exposure to the upper leg, which was significantly greater than for other body parts.…”
Section: Discussionmentioning
confidence: 47%
“…However, with crops cultivated in submerged conditions, such as rice, pesticide exposure occurs often across the lower body (shins, thighs, and hips). Here, when spraying onto lower crops (about 80–100 cm high), workers are exposed while moving . Thus, the pesticide exposure observed within the present study (with low‐lying Korean cabbage, spraying in a downward trajectory with a long wand sprayer) was robust on the legs.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Another field factor that positively correlated with the levels of ADDA was the number of spray tanks applied by the applicators (r = 0.53, p > 0.05). Some research has shown that hand contamination can be the highest contributor to total exposure among pesticide applicators (Atabila et al 2017;Baldi et al 2006;Machera 2003;Vitali et al 2009), with the most hand contamination occurring during mixing and loading of pesticides into spray tanks (Gao et al 2014;Kim et al 2014). None of the applicators in the present study used hand gloves, a situation that predisposed them to direct hand contamination.…”
Section: Factors Associated With Absorbed Daily Dose Of Chlorpyrifos mentioning
confidence: 99%